Development and performance evaluation of a cablegation system for surface irrigation - GEETHA S; Prasad V. P; Vinodkumar P.R; Er. Rema K. P (Guide) (Tavanur 1996 Department of Land and Water Resources and Conservation Engineering)
Development and performance evaluation of a cablegation system for surface irrigation
Development and performance evaluation of a cablegation system for surface irrigation